Magnetic Nanoparticles Coated with (R)-9-Acetoxystearic Acid for Biomedical Applications - Micheletti, Gabriele (ACS Omega, 2020)
[Image: see text] The well-known ability to selectively drive nanomagnetic materials coated with anticancer drugs into tumor cells suggested the synthesis and the characterization of magnetic nanoparticles (MNPs) functionalized with (R)-9-acetoxystearic acid, the acetic ester of (R)-9-hydroxystearic acid (9-HSA), an antiproliferative agent active against different cancer cells. The acyl chloride of (R)-9-acetoxystearic acid, synthesized in two steps from 9-HSA, was reacted with (3-aminopropyl)triethoxysilane, chosen as a linker between MNPs and the stearyl moiety. In the last step, the novel amide was bound to magnetite NPs by reaction with silyl groups. A detailed structural, chemical, and magnetic characterization of the obtained material proved that it possesses properties in agreement with the requirements for drug delivery, opening the possibility to further insights focused on the 9-HSA biomedical applications.